1996
DOI: 10.1212/wnl.47.1.76
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the electroencephalogram in antiepileptic drug withdrawal in partial epilepsies

Abstract: We evaluated the prognostic value of the EEG in 120 seizure-free epileptic patients (49 with complex partial seizures with or without episodic secondarily generalization [CPS], 20 with simple partial seizures with or without episodic secondarily generalization [SPS], 51 with only secondarily generalized seizures [PSG] during and after antiepileptic drug withdrawal. All patients had EEG examination before; during; and 3, 12, 24, and 36 months after drug withdrawal. Relapse rates were 45% in CPS, 100% in SPS, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 5 publications
0
22
1
1
Order By: Relevance
“…Anderson et al observed that patients with epileptiform waves on their EEG prior to therapy discontinuation were more likely to experience recurrence compared to those who did not have epileptiform waves (67% versus 33%) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al observed that patients with epileptiform waves on their EEG prior to therapy discontinuation were more likely to experience recurrence compared to those who did not have epileptiform waves (67% versus 33%) [16].…”
Section: Discussionmentioning
confidence: 99%
“…It found that although the interictal EEG at time of antiepileptic drug withdrawal did not predict recurrence, a worsening of the EEG after withdrawal was predictive of seizure recurrence. 4 …”
Section: Resultsmentioning
confidence: 99%
“…3 One study reported 63% of patients with partial seizures relapsed on drug withdrawal. 4 Remote symptomatic seizures (defined as seizures occurring in patients with a prior neurologic insult such as head injury, stroke or history of intellectual disability) are associated with a high risk of seizure relapse following discontinuation of therapy. 2 …”
Section: Factors Influencing Relapsementioning
confidence: 99%
“…Besides diagnosis and monitoring of the disease, the relevance of EEG has been studied in a third situation: when the epilepsy seems well controlled, with no seizures over the course of several years, can the treatment be stopped and does the EEG have a real predictive value for evaluating the risk of recurrence after treatment withdrawal? The few prospective studies that included EEG in their protocol found a greater risk of seizure recurrence in cases with abnormal EEG [1,30,155], except for two of them, whose negative results might easily be explained by selection bias. Indeed, decision to withdraw or not the treatment was partly based upon EEG results [147], and paroxysmal EEG abnormalities could even be an exclusion factor if generalized [105].…”
Section: Relevance Of Eeg As a Predictive Factor For The Risk Of Seizmentioning
confidence: 99%
“…Indeed, decision to withdraw or not the treatment was partly based upon EEG results [147], and paroxysmal EEG abnormalities could even be an exclusion factor if generalized [105]. Finally, timing seems essential since Tinuper et al [155] found a predictive value when EEG became abnormal during the withdrawal process, but not if the abnormalities were already present before beginning drug withdrawal.…”
Section: Relevance Of Eeg As a Predictive Factor For The Risk Of Seizmentioning
confidence: 99%